FACTORS INFLUENCING THE CONDITIONS OF OPEN PIT MINING, ORE MASS AND DEFORMATION, PROCESSES THAT LEAD TO IMBALANCE DURING EXCAVATION - Djaksimuratov Karamatdin Mustapaevich; O’telbayev Azizbek Alisher o’g’li; O’razmatov Jonibek Ikromboy o’g’li; Maulenov Nurlibek Axmetovich (Galaxy International Interdisciplinary Research Journal, 2021)
Mining enterprises, geotechnological processes in the field, the state of open pit mining,processing processes as a result of the development of mining and extraction processes.